Relationship between strength, technique, and tactics with canoe slalom performance - Pratt, J. (Simon Fraser University, 2022)
This research investigates the relationships between strength, technique, and tactics in canoe slalom. 15 C1 athletes paddled a white-water slalom course and a flat-water figure 8 course. Paddle forces, GPS data, and accelerations were collected to form a set of performance metrics. Relationships between performance metrics on flat-water or white water with white-water race times were assessed through multiple regression. Additionally, the relationship between flat-water paddle force and flat-water lap time was modelled using a mixed effects model. White-water race times were successfully predicted using flat-water or white-water performance metrics (r2 = 0.81 and 0.98 respectively). Flat water lap time was significantly related to paddle force. Despite high correlations with white-water race time, the figure-8 test alone lacked predictive power. The figure-8 test could be a training tool for athletes and coaches to monitor improvements in paddling specific strength. On white-water, athletes relied on high speeds, shorter distances and power to achieve fast times.